1987
DOI: 10.2170/jjphysiol.37.393
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the low resting membrane potentials of diseased human atrial muscles.

Abstract: we studied the ionic mechanism of low resting potential (RP) of quiescent "diseased" human atrial fibers. The RP was -49.7 ± 0.8 mV (n= 179) in normal Tyrode's solution (5.4 mM [K]0, 36°C). The changes in RP measured at various levels of [K]0 appeared to fit the RP-[K]0 relationship predicted by the Goldman-Hodgkin-Katz equation, assuming PNa/PK ratio (a) to be 0.102 and [K]; to be 131.9 mM. The a far exceeded the normal value (about 0.01) by a factor of 10. Acetylcholine (ACh, 10 /1M) led to marked increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This finding was not expected and has not heretofore been reported. It is interesting to speculate that severe stretches increased gK1 and resulted in hyperpolarization, since 1) the hyperpolarization occurred predominantly in relatively lower [K+]0 in which gK1 is expected to be low (KAMEYAMA et al, 1983), and 2) the direction of changes in the RP-[K+]0 relationship produced by a severe stretch was just opposite to that reported in the case of atrial muscles having decreased gK1 (IMANISHI and ARITA, 1987). The hyperpolarization may not be due to the increase in [K+]; or increased equilibrium potential for K+, because 3 curves in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…This finding was not expected and has not heretofore been reported. It is interesting to speculate that severe stretches increased gK1 and resulted in hyperpolarization, since 1) the hyperpolarization occurred predominantly in relatively lower [K+]0 in which gK1 is expected to be low (KAMEYAMA et al, 1983), and 2) the direction of changes in the RP-[K+]0 relationship produced by a severe stretch was just opposite to that reported in the case of atrial muscles having decreased gK1 (IMANISHI and ARITA, 1987). The hyperpolarization may not be due to the increase in [K+]; or increased equilibrium potential for K+, because 3 curves in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The resting membrane potential of the right atrial muscle excised from the patients with congenital or acquired heart disease ("diseased atrial muscle") is generally decreased, probably due to chronic hemodynamic overload or ischemia that might have been imposed on the atrium for a long period of time (MARY-RABINE et al, 1983;LEE, 1986;IMANISHI and ARITA, 1987). In the present study using such "diseased right atrial muscles ," we measured aK and Vm in non-driven conditions and found the a K to be 99.7 + 1.3 mM and the Vm, -43.9±1.4 mY.…”
Section: Discussionmentioning
confidence: 99%
“…Diseased human atrial fibers are characterized by low, non-uniform levels of the resting membrane potential (TEN EICK and SINGER, 1979;MARY-RABINE et al, 1983;IMANISHI and ARITA, 1987). Such changes have been attributed to non-homogeneous decreases in the resting K+ conductance (TEN Elck and SINGER, 1979), increases in the resting Na + conductance (IMANISHI and ARITA, 1987), and impairment of the electrogenic Na-K pump (LEE, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the notion that activation of 'Ca contributes to the pacemaker potential of the slow-type AAPs. However, it must be remembered that in diseased human atrial muscles, the resting potassium conductance (gK,) is generally decreased, and the resting sodium conductance considerably increased (IMANISHI and ARITA, 1987). Such conditions are responsible for the low resting potential of these preparations and certainly favour the development of both "slow-" and "fast-"type AAPs.…”
Section: Discussionmentioning
confidence: 99%